Induction Of Mastitis In Rabbit Mammary Glands With Bovine Mastitis Bacterial Strains - KAVITHA G; S ISLOOR; D RATHNAMMA; Y B RAJESHWARI; C S NAGARAJA; S SADISH (International Journal of Pharma and Bio Sciences, 2011)
An experimental model was developed in rabbits to study bovine mastitis. Six lactating rabbits for each isolate were used to induce mastitis by using highly prevalent E.coli O9 and O147 isolates from bovine mastitis cases that possessed three different virulent genes. In the study, 104, 105, 106 and 107 cfu/ml of E.coli bacterial suspensions were inoculated in to each pair of teats via the base of the teat and to the first pair, 1 ml of PBS was administered. Gross lesions were recorded for 6 days post inoculation. Milk samples were collected from zero days, up to 144 hrs. Mastitis was induced as indicated by an increase in SCC, positivity with CMT and increase in total viable bacterial counts in milk. The macroscopic lesions were very well appreciated in all the infected quarters at 48 hrs post infection. The results in the present study clearly showed that both the serotypes induced mastitis in rabbits.